Studies on gene polymorphisms in sports.Fancy fashion or important field of research? - Appell Coriolano, H.-J.; Duarte, J. A. (International Journal of Sports Medicine, 2012)
The influence of genetic vs. environmental factors on physical characteristics or sports performance has attracted the interest of researchers for many decades, resulting in a large number of twin studies. Beyond comparing only the phenotype of obviously identical genotypes, new strategies allowed the study of the influence of the genome on structural and functional human characteristics. There is no doubt that an orchestrated expression of the human genome is determinant to explain human individuality in sports performance.